1983
DOI: 10.2166/wst.1983.0172
|View full text |Cite
|
Sign up to set email alerts
|

Granulation in UASB-Reactors

Abstract: The influence of the sludge loading rate, the addition of a small amount of granular sludge to the seed sludge and the effect of the NH4+- and Ca2+-concentration in the influent on the pelletization-process of anaerobic methanogenic sludge in UASB-reactors were studied. Two different types of sludge granules can be obtained with VFA's as feed-solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
0
12

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(109 citation statements)
references
References 0 publications
3
94
0
12
Order By: Relevance
“…Besides the benefit of increased gas production, the biomass loading rate also provides the energy and starting materials for biosynthetic 101 processes. Therefore, as the biomass loading rate is increased, there is more capacity for cell growth and, thus, for granule formation.By combining the three forces of hydraulic, gas, and biomass loading rates, it is hypothesized that granulation can be stimulated at an early stage of UASB operation.Reports of granulation in as few as 30 days have been reported in UASB reactors by controlling these parameters [21,66,67,68]. The minimum biomass loading rates required for rapid granulation have been reported as 0.6 g COD/g VSS/day [67], although more recent studies have observed granulation at lower biomass loading rates [5,66,68].…”
mentioning
confidence: 99%
“…Besides the benefit of increased gas production, the biomass loading rate also provides the energy and starting materials for biosynthetic 101 processes. Therefore, as the biomass loading rate is increased, there is more capacity for cell growth and, thus, for granule formation.By combining the three forces of hydraulic, gas, and biomass loading rates, it is hypothesized that granulation can be stimulated at an early stage of UASB operation.Reports of granulation in as few as 30 days have been reported in UASB reactors by controlling these parameters [21,66,67,68]. The minimum biomass loading rates required for rapid granulation have been reported as 0.6 g COD/g VSS/day [67], although more recent studies have observed granulation at lower biomass loading rates [5,66,68].…”
mentioning
confidence: 99%
“…Immobilization further requires the presence of support material and/or specific growth nuclei (Hulshoff Pol et al 1983), as well as the presence of exopolymeric substances (EPS) acting as a kind of glue creating a microbial matrix (Vanderhaegen et al 1992). The occurrence of granulation can be explained as follows:…”
Section: Sludge Granulationmentioning
confidence: 99%
“…Therefore, at due time, particles/films will fall apart, evolving a next generation. The first generation(s) of aggregates, indicated by Hulshoff Pol et al (1983) as ''filamentous'' granules, are quite voluminous and in fact more a flock than a granule.…”
Section: Sludge Granulationmentioning
confidence: 99%
“…The performance and stability of these reactors depend a lot on sludge granulation, but the success of the self-immobilization process is not warranted, since several factors affect this process (Kalyuzhnyi et al, 1996;Hulshoff-Pol et al, 1983). According to Liu et al (1993), the UASB reactor is highly dependent on the granulation process, unlike anaerobic sequencing batch reactors.…”
Section: Introductionmentioning
confidence: 99%
“…High settling velocities and high specific activity are the characteristics that are most important for efficient biomass retention in the reactor and high waste biodegradation (Lettinga et al, 1980;Hulshoff-Pol et al, 1983). Anaerobic granular sludge consists of dense multi-species microbial communities.…”
Section: Introductionmentioning
confidence: 99%